Medicine meets virtual reality: the convergence of physical and informational technologies: options for a new era in health care - Westwood, James D.; Hoffman, H.M.; Robb, R.A.; Stredney, D. (Studies in health technology and informatics, 1998)
Title page -- Preface -- Contents -- Telepathology in Neurosurgery -- A System for the Simulation and Planning of Orthodontic Treatment using a Low Cost 3D Laser Scanner for Dental Anatomy Capturing -- The Use of an Information Architecture Modeling Tool in the Development of Disease Management Systems -- Deformation Simulation Algorithms of Elastic Tissues in "Real-Time" Based in Elasticity Theory -- Anatomical and Physiological Models for Surgical Simulation -- Automatic modeling of knee joint motion for the Virtual Reality Dynamic Anatomy (VRDA) tool -- CathSim -- Simulation of Tissue Cutting and Bleeding for Laparoscopic Surgery Using Auxiliary Surfaces -- An Improved Stereotactic Technique for Cyst Cannulation -- A Virtual Instrument Ergonomics Workstation To Measure Surgeons' Physical Stress -- Fast Finite Element Modeling for Surgical Simulation -- Defining The Role Of Haptic Feedback In Minimally Invasive Surgery -- Haptic rendering of isosurfaces directly from medical images -- Realtime Simulation of Tissue Deformation for the Nasal Endoscopy Simulator (NES) -- Preop™ Endoscopic Simulator: A PC-Based Immersive Training System for Bronchoscopy -- Hierarchical Decomposition of Laparoscopic Procedures -- Virtual Reality: A Wholistic Approach to Rehabilitation -- Thin Walled Models for Haptic and Graphical Rendering of Soft Tissues in Surgical Simulations -- Efficient Linear Elastic Models of Soft Tissues for real-time surgery simulation -- Stereo Augmented Reality in the Surgical Microscope -- A New Hybrid Renderer for Virtual Bronchoscopy -- Visual Clues In Minimally Invasive Surgery: Use Of 2-D Versus 6-D Enhanced Performance of Complex Minimally Invasive Complex Skills -- Evaluation of Skill Acquisition Using a Force Feedback, Virtual Reality Based Surgical Trainer